2017
DOI: 10.1037/abn0000240
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessment of negative symptoms in schizophrenia: Relationships to effort-based decision making and reinforcement learning.

Abstract: Negative symptoms are a core clinical feature of schizophrenia, but conceptual and methodological problems with current instruments can make their assessment challenging. One hypothesis is that current symptom assessments may be influenced by impairments in memory and may not be fully reflective of actual functioning outside of the laboratory. The present study sought to investigate the validity of assessing negative symptoms using ecological momentary assessment (EMA). Participants with schizophrenia (N=31) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 42 publications
(71 reference statements)
5
56
2
2
Order By: Relevance
“…An emerging trend in affective neuroscience has been to increase functional relevance of experimental findings by investigating hedonic and goal‐directed behaviour using laboratory paradigms in conjunction with ESM. Moran et al linked blunted daily‐life experience of pleasure and motivation to poorer performance on effort and reward learning tasks in individuals with schizophrenia. Our group combined ESM with neuromolecular imaging in healthy individuals with increased familial risk for psychosis.…”
Section: Applications Of Esm In the Mental Health Research Fieldmentioning
confidence: 99%
“…An emerging trend in affective neuroscience has been to increase functional relevance of experimental findings by investigating hedonic and goal‐directed behaviour using laboratory paradigms in conjunction with ESM. Moran et al linked blunted daily‐life experience of pleasure and motivation to poorer performance on effort and reward learning tasks in individuals with schizophrenia. Our group combined ESM with neuromolecular imaging in healthy individuals with increased familial risk for psychosis.…”
Section: Applications Of Esm In the Mental Health Research Fieldmentioning
confidence: 99%
“…Further, extant studies examining the association between these tasks and clinician-rated negative symptoms have yielded mixed results. For example, some studies using forced-choice non-adaptive reward tasks have found small but significant inverse associations (Barch et al, 2014;Horan et al, 2015), while others have failed to find significant associations (Fervaha, Duncan, et al, 2015;Moran et al, 2017), found a trend level association (Treadway et al, 2015), or even an unexpected positive association with clinician-rated negative symptoms (McCarthy et al, 2016). On the other hand, compared to forced-choice non-adaptive reward tasks, some studies examining the magnitude of the relationship between both effort discounting and progressive ratio tasks and clinician-rated negative symptoms have found relatively stronger associations with negative symptoms (i.e., medium to large (Culbreth et al, 2016;Strauss et al, 2016;Wolf et al, 2014); but also see Bismark et al, 2018& Docx et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of an association between the clinical assessments of apathy and the effort-choice performance thus suggests that the clinical assessments capture apathy unreliably, which may be the key reason for the lack of association between activity measures and apathy. This is not surprising, as the key features of apathy cannot be observed in the interview but have to be elicited by the clinician and rely primarily on the patient's memory and report, which has been shown to negatively affect the accuracy of symptom reporting (36). Not surprisingly, we found the highest correlation between the expressive deficit scores and gesture count and power.…”
Section: Discussionmentioning
confidence: 53%